ANALISIS KADAR SERUM GLUTAMIC PIRUVIC TRANSAMINASE DAN SERUM GLUTAMIC OXALOACETIC TRANSAMINASE PADA PASIEN TUBERKULOSIS YANG MENJALANI PENGOBATAN OBAT ANTI TUBERKULOSIS - Salbiah, Salbiah; Diah Lestari; Dina Indarsita; Halimah Fitriani Pane; Yasmine Amira Fadila (Poltekkes Kemenkes Medan, 2024)
Introduction: Since 1995, Indonesia began to adopt the Directly Observed Treatment Shortcourse Chemotherapy (DOTS) system in controlling tuberculosis. The main drugs recommended in this system are Antituberculosis Drugs (OAT) consisting of Isoniazid (H), Rifampicin (R), Pyrazinamide (Z), and Ethambutol (E). The use of Anti-Tuberculosis Drugs can cause side effects which are still other problems, such as liver damage which is characterized by an increase in transaminase enzymes. Therefore, monitoring liver function is very important. The routine examination carried out is a serum transaminase examination, namely SGOT (AST) and SGPT (ALT). Therefore, monitoring liver function is very important. The routine examination carried out is a serum transaminase examination, namely SGOT (AST) and SGPT (ALT). Objective: the aim of this study is to determine whether there is a difference between SGOT and SGPT levels before and after treatment with Antituberculosis Drugs . Method: The research design was cross-sectional analytic using secondary data from examination results of SGOT and SGPT levels from adult tuberculosis sufferers who were undergoing treatment at Cileungsi Regional Hospital, totaling 70 people. The research was conducted from January to August 2023. Results: There was an increase in SGOT levels by 104%, namely from 21.61 IU/L before treatment to 43.47 IU/L and SGPT levels increased by 107%, namely from 16.41 IU/L before treatment to 34.47 IU /L.. The Wilcoxon test showed a significant difference of 0.000 (p <0.05) for SGOT and SGPT levels before and after treatment.. Conclusion: there is a significant difference between SGOT and SGPT levels before and after treatment with antituberculosis drugs.